Patch clamp probe for testing state density of material and use method of patch clamp probe
By designing patch clamp probes, integrating electrolyte and electrodes, and moving the probes to approach the surface of the micro-nano energy storage device, the problem of traditional tests not being able to understand the electrochemical contribution of local active sites is solved, and the electrochemical normal state density characterization of different sites of the micro-nano energy storage device is realized, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202411827817.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Electrochemical testing of devices on traditional micro-nano energy storage chips can only obtain average information on the contribution of all active sites in the material window area, and it is impossible to understand the true contribution of local active sites, and it is difficult to distinguish the electrochemical contribution of local active sites in the material.
A patch clamp probe is designed to integrate electrolyte, electrolyte cell, counter electrode and reference electrode. The patch clamp probe is moved through a three-dimensional mobile device to approach the surface of the device on the micro-nano energy storage chip to be tested, so as to achieve the testing of electrochemical normal state density information at different sites and regions.
By testing the local electrochemical information of different sites of the device on the same micro-nano energy storage chip, the state density information of different sites can be obtained, and the electrochemical method state density characterization of different active sites of the device on the same micro-nano energy storage chip is achieved, simplifying the preparation process and reducing the cost of raw materials.
Smart Images

Figure CN119643363A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of micro-nano energy storage devices, and particularly relates to a patch clamp probe for testing material state density and a use method thereof. Background Art
[0002] As a micro-device for electrochemical testing with unique advantages, micro-nano energy storage chip devices can measure the electrochemical information in the material window area compared to the electrochemical testing of traditional materials. However, the electrochemical testing of traditional micro-nano energy storage chip devices can only obtain the average information of the contribution of all active sites in the window area, but cannot understand the true contribution of local active sites, so it is difficult to distinguish the electrochemical contribution of local active sites in various materials.
[0003] Therefore, we independently designed a patch clamp probe to integrate the electrolyte, electrolytic cell, counter electrode and reference electrode for electrochemical testing of traditional micro-nano energy storage on-chip devices. The patch clamp probe is moved by a three-dimensional mobile device to approach the surface site of the micro-nano energy storage on-chip device to be tested. This can not only simplify the preparation process of the micro-nano energy storage on-chip devices, but also realize the electrochemical state density characterization of different active sites of the same micro-nano energy storage on-chip device. Summary of the invention
[0004] The purpose of the present invention is to provide a patch clamp probe for testing material state density. By integrating the electrolyte, electrolytic cell, counter electrode and reference electrode of a conventional micro-nano energy storage chip device, the electrochemical state density information of different sites and regions of the chip device can be tested.
[0005] In order to achieve the above-mentioned purpose, the present application provides a patch clamp probe for testing the state density of a material, characterized in that the patch clamp probe includes a patch clamp pipette, a custom polytetrafluoroethylene sleeve, a reference electrode and a counter electrode, the patch clamp pipette is drawn from a glass tube, and a tip structure is formed at one end of the patch clamp pipette by drawing, and both ends of the patch clamp pipette have openings, wherein the inner diameter of the opening on the side with the tip structure is smaller than the inner diameter of the opening on the other side, the middle part of the custom polytetrafluoroethylene sleeve is provided with a through hole adapted to the outer diameter of the pipette, and two blind holes are symmetrically arranged at both ends of the through hole, and the patch clamp pipette is far One side away from the tip structure is fixedly installed in the through hole of the customized polytetrafluoroethylene sleeve, and conductive copper rods are respectively installed in the two blind holes at the upper end of the customized polytetrafluoroethylene sleeve, and the conductive copper rods are symmetrically distributed relative to the patch clamp pipette. The patch clamp pipette is filled with electrolyte, and the reference electrode and the counter electrode are inserted into the patch clamp pipette from the side with a larger opening of the patch clamp pipette and contact with the electrolyte. The patch clamp probe also includes a sealing rubber cap, which fixes the reference electrode and the counter electrode and seals the opening on the side where the electrode is located, and the reference electrode and the counter electrode are respectively conductively connected to the conductive copper rods.
[0006] Furthermore, the inner diameter of the tip of the patch clamp pipette is 200 nm-1000 nm.
[0007] Furthermore, the reference electrode is an Ag / AgCl reference electrode, which is obtained by constant current electrodeposition, specifically, a pure Ag wire is used as a working electrode and immersed in an HCl solution, and a commercial Pt electrode is used as a counter electrode and prepared by constant current electrodeposition.
[0008] Furthermore, the counter electrode is a Pt counter electrode, and the Pt counter electrode is prepared by Pt metal wire.
[0009] Furthermore, the electrolyte may be one of a 0.5 mol / L sulfuric acid solution, a hydroxymethylferrocene solution or a BMMIBF4 solution.
[0010] Furthermore, the glass tube is made of one of borosilicate glass, lead glass, laminated glass and ceramic glass.
[0011] Furthermore, the inner diameter of the glass tube is 0.5-3 mm, and the outer diameter is 1-5 mm.
[0012] Furthermore, the diameter of the Ag / AgCl reference electrode is 0.1-0.3 mm; the diameter of the Pt counter electrode is 0.1-0.3 mm.
[0013] The present invention also provides a method for testing the state density of a material using the patch clamp probe described above, comprising the following steps: (1) Place a micro-nano energy storage chip device on a three-dimensional movable micro-probe platform, press the metal probe of the micro-probe platform onto the gold electrode of the chip device as a wire connecting the working electrode to the electrochemical workstation; (2) Fix the patch clamp probe on the three-axis movable probe clamp of the scanning electrochemical microscope, and connect the reference electrode and counter electrode of the patch clamp probe to the electrochemical workstation; (3) Using a scanning electrochemical microscope, the tip of the patch clamp probe is brought close to the surface site of the micro-nano energy storage device to be tested. By adjusting the electrochemical test parameters, electrochemical tests are performed on different sites of the same micro-nano energy storage device to obtain the state density information of the material on the micro-nano energy storage device.
[0014] Furthermore, the micro-nano energy storage chip device includes a silicon base layer, a silicon dioxide layer on the surface of the silicon base layer, a gold electrode layer with a regular pattern arranged on the surface of the silicon dioxide, and the material to be tested is deposited on the silicon dioxide layer and conductively connected to the gold electrode with the regular pattern.
[0015] Beneficial effects of the present invention: The present invention integrates electrolyte, electrolytic cell, counter electrode and reference electrode by adopting patch clamp probe, and moves the patch clamp probe by three-dimensional moving device to approach the surface of the micro-nano energy storage chip device to be tested, which can not only simplify the preparation process of the micro-nano energy storage chip device, but also obtain the state density information of different sites by testing the local electrochemical information of different sites of the same on-chip device, thereby realizing the electrochemical state density characterization of different active sites of the same micro-nano energy storage chip device. At the same time, the patch clamp probe of the present application has a simple manufacturing process and low raw material cost. At the same time, different probe systems can be prepared according to different materials and have good adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the structure of the embodiment is briefly described below with reference to the accompanying drawings.
[0017] Figure 1 Schematic diagram of the overall structure of the micro-nano energy storage on-chip device test provided by the embodiment of the present invention Figure 2 Schematic flow chart of the preparation of the patch clamp probe provided in the embodiment of the present invention Figure 3 Physical flow chart of the preparation of the patch clamp probe provided in the embodiment of the present invention Figure numerals: 1 - patch clamp pipette; 2 - electrolyte; 3 - polytetrafluoroethylene custom sleeve; 4 - conductive copper rod; 5 - Pt electrode; 6 - Ag / AgCl electrode; 7 - sealing rubber cap. DETAILED DESCRIPTION
[0018] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0019] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0020] Figure 2 A schematic flow chart of the preparation of a patch clamp probe provided in an embodiment of the present invention, wherein Figure 2 It can be determined that the patch clamp probe includes a patch clamp pipette and a custom polytetrafluoroethylene sleeve, the patch clamp pipette is drawn from a glass tube, one end of the patch clamp pipette forms a tip structure, and both ends have openings, wherein the inner diameter of the opening on the side with the tip structure is smaller than the inner diameter of the opening on the other side, a through hole matching the outer diameter of the pipette is provided in the middle portion of the custom polytetrafluoroethylene sleeve, and two blind holes are symmetrically arranged at both ends of the through hole, and the side of the patch clamp pipette away from the tip structure is fixedly mounted on the through hole of the custom polytetrafluoroethylene sleeve The hole is provided with conductive copper rods in two blind holes at the upper end of the custom polytetrafluoroethylene sleeve, and the conductive copper rods are symmetrically distributed relative to the patch clamp pipette. The patch clamp pipette is filled with electrolyte, and the Ag / AgCl reference electrode and the Pt counter electrode are inserted into the electrolyte from the opening on the other side of the patch clamp pipette relative to the tip side, and the opening is sealed by a sealing rubber cap, and the Ag / AgCl reference electrode and the Pt counter electrode are fixed at the same time, and the reference electrode and the counter electrode are conductively connected to the conductive copper rods respectively.
[0021] The patch clamp pipette is drawn using a needle puller (HL-1000). The glass tube used is made of borosilicate. The glass tube is 10 cm long, 1.5 mm in outer diameter, 1.0 mm in inner diameter, and 0.25 mm in wall thickness. The tip of the pipette obtained by drawing has an outer diameter of 600 nm, an inner diameter of 500 nm, and a wall thickness of 100 nm.
[0022] The Ag / AgCl reference electrode is obtained by constant current electrodeposition. A pure Ag wire with a diameter of 0.1 mm is used as a working electrode and immersed in a 0.1 mol / L HCl solution. A commercial Pt electrode is used as a counter electrode for constant current electrodeposition. The electrodeposition current is 0.0003 mA and the deposition time is 10 mins.
[0023] The Pt counter electrode is a Pt metal wire with a diameter of 0.1 mm.
[0024] The custom polytetrafluoroethylene sleeve is a cylinder with a diameter of 10 mm and a height of 8 mm, with a through hole with a diameter of 1.5 mm in the middle and two blind holes with a side length of 2 mm at both ends.
[0025] The conductive copper rod is a T2 copper rod with a side length of 2 mm and a length of 3 cm.
[0026] The sealing rubber is a black rubber cap with a diameter of 1.3 mm.
[0027] Furthermore, in a preferred embodiment of the present invention, the electrolyte may be 0.5 mol / L sulfuric acid, hydroxymethylferrocene solution or other solutions such as BMMIBF4.
[0028] Figure 3 The structural assembly diagram of the patch clamp probe for testing the material state density is as follows: Step 1: Place a borosilicate glass tube with an outer diameter of 1.5 mm and an inner diameter of 1.0 mm on a needle puller (HL-1000) and pull it to obtain a patch clamp pipette with a tip outer diameter of 600 nm and an inner diameter of 500 nm.
[0029] Step 2: Use a micro syringe to slowly inject the electrolyte into the patch clamp pipette, and blow air under pressure at the end of the pipette to expel bubbles, ensuring that the electrolyte is completely conductive in the pipette.
[0030] Step 3: Fix the two conductive copper rods to the blind holes at both ends of the custom polytetrafluoroethylene sleeve, and then fix the sleeve to the appropriate position at the end of the patch clamp pipette.
[0031] Step 4: Place the homemade 0.1mm diameter Ag / AgCl electrode and Pt electrode in appropriate positions of the patch clamp pipette.
[0032] Step 5: Seal the base of the patch clamp pipette with a rubber cap to prevent the electrolyte from evaporating.
[0033] Step 6: Use solder to connect the 0.1 mm Ag / AgCl electrode and Pt electrode to the conductive copper rods at both ends of the custom polytetrafluoroethylene sleeve.
[0034] Figure 1 The overall structure diagram of the micro-nano energy storage chip device test is shown in FIG. The method of testing the material state density using a patch clamp probe includes the following steps: (1) Place a micro-nano energy storage chip device on a three-dimensional movable micro-probe platform, press the metal probe of the micro-probe platform onto the gold electrode of the chip device as a wire connecting the working electrode to the electrochemical workstation; (2) Fix the patch clamp probe on the three-axis movable probe clamp of the Chenhua scanning electrochemical microscope, and connect the Ag / AgCl metal wire and Pt wire of the patch clamp probe to the electrochemical workstation as the reference electrode and counter electrode respectively; (3) Using a scanning electrochemical microscope, the tip of the patch clamp probe is brought close to the surface site of the micro-nano energy storage device to be tested. By adjusting the electrochemical test parameters, electrochemical tests are performed on different sites of the same micro-nano energy storage device to obtain the state density information of the material on the micro-nano energy storage device.
[0035] The micro-nano energy storage chip device includes a silicon base layer, a silicon dioxide layer on the surface of the silicon base layer, and a gold electrode layer with a regular pattern on the surface of the silicon dioxide. The material to be tested is deposited on the silicon dioxide layer and is conductively connected to the gold electrode with the regular pattern.
[0036] By using a patch clamp probe to integrate the electrolyte, electrolytic cell, counter electrode and reference electrode, and moving the patch clamp probe through a three-dimensional mobile device to approach the surface of the micro-nano energy storage chip device to be tested, not only can the preparation process of the micro-nano energy storage chip device be simplified, but also by testing the local electrochemical information of different sites on the same on-chip device, the state density information of different sites can be obtained, and the electrochemical state density characterization of different active sites of the same micro-nano energy storage chip device can be achieved. At the same time, the patch clamp probe of the present application has a simple manufacturing process and a low raw material cost. At the same time, different probe systems can be prepared according to different materials and have good adaptability.
[0037] The above are only exemplary embodiments of the present disclosure, and the scope of the present disclosure cannot be limited thereto. That is, any equivalent changes and modifications made according to the teachings of the present disclosure are still within the scope of the present disclosure. After considering the disclosure of the specification and the truth of practice, it will be easy for those skilled in the art to think of other embodiments of the present disclosure. This application is intended to cover any variation, use or adaptive change of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the technical field that are not recorded in the present disclosure.
Claims
1. A patch clamp probe for testing material state density, characterized in that: The patch clamp probe comprises a patch clamp pipette, a custom polytetrafluoroethylene sleeve, a reference electrode and a counter electrode. The patch clamp pipette is drawn from a glass tube, and a tip structure is formed at one end of the patch clamp pipette by drawing. Both ends of the patch clamp pipette have openings, wherein the inner diameter of the opening on the side with the tip structure is smaller than the inner diameter of the opening on the other side. A through hole matching the outer diameter of the pipette is provided in the middle portion of the custom polytetrafluoroethylene sleeve, and two blind holes are symmetrically arranged at both ends of the through hole. The side of the patch clamp pipette away from the tip structure is fixedly mounted on the polytetrafluoroethylene sleeve. Conductive copper rods are respectively installed in the through hole of the customized polytetrafluoroethylene sleeve and the two blind holes on the upper end of the customized polytetrafluoroethylene sleeve, and the conductive copper rods are symmetrically distributed relative to the patch clamp pipette. The patch clamp pipette is filled with electrolyte, and the reference electrode and the counter electrode are inserted into the patch clamp pipette from the side with the larger opening of the patch clamp pipette and contact with the electrolyte. The patch clamp probe also includes a sealing rubber cap, which fixes the reference electrode and the counter electrode and seals the opening on the side where the electrode is located. The reference electrode and the counter electrode are respectively conductively connected to the conductive copper rods.
2. The patch clamp probe for testing material state density according to claim 1, characterized in that: The inner diameter of the patch clamp pipette tip is 200 nm-1000 nm.
3. The patch clamp probe for testing material state density according to claim 1, characterized in that: The reference electrode is an Ag / AgCl reference electrode, which is obtained by constant current electrodeposition, specifically, by immersing a pure Ag wire as a working electrode in an HCl solution and performing constant current electrodeposition on a commercial Pt electrode as a counter electrode.
4. The patch clamp probe for testing material state density according to claim 1, characterized in that: The counter electrode is a Pt counter electrode, and the Pt counter electrode is prepared by Pt metal wire.
5. The patch clamp probe for testing material state density according to claim 1, characterized in that: The electrolyte may be one of a 0.5 mol / L sulfuric acid solution, a hydroxymethylferrocene solution or a BMMIBF4 solution.
6. The patch clamp probe for testing material state density according to claim 1, characterized in that: The glass tube is made of one of borosilicate glass, lead glass, laminated glass and ceramic glass.
7. The patch clamp probe for testing material state density according to claim 1, characterized in that: The inner diameter of the glass tube is 0.5-3 mm, and the outer diameter is 1-5 mm.
8. The patch clamp probe for testing material state density according to claim 3 or 4, characterized in that: The diameter of the Ag / AgCl reference electrode is 0.1-0.3 mm; the diameter of the Pt counter electrode is 0.1-0.3 mm.
9. A method for testing the state density of a material using the patch clamp probe according to any one of claims 1 to 8, comprising the following steps: (1) Place a micro-nano energy storage chip device on a three-dimensional movable micro-probe platform, press the metal probe of the micro-probe platform onto the gold electrode of the chip device as a wire connecting the working electrode to the electrochemical workstation; (2) Fix the patch clamp probe on the three-axis movable probe clamp of the scanning electrochemical microscope, and connect the reference electrode and counter electrode of the patch clamp probe to the electrochemical workstation; (3) Using a scanning electrochemical microscope, the tip of the patch clamp probe is brought close to the surface site of the micro-nano energy storage device to be tested. By adjusting the electrochemical test parameters, electrochemical tests are performed on different sites of the same micro-nano energy storage device to obtain the state density information of the material on the micro-nano energy storage device.
10. The method according to claim 9, characterized in that The micro-nano energy storage chip device includes a silicon substrate layer, a silicon dioxide layer on the surface of the silicon substrate layer, a gold electrode layer with a regular pattern arranged on the surface of the silicon dioxide, and the material to be tested is deposited on the silicon dioxide layer and is conductively connected to the gold electrode with a regular pattern.
Citation Information
Patent Citations
Epitaxial wafer, manufacturing method thereof and electrochemical sensor
CN111912886A
Nanometer material single crystal stress field coupling electrochemical testing device and method
CN114354726A
Monopole composite microelectrode system for cardiac activity mapping and preparation method thereof
CN117179773A
Microprobe and electrical measurement system using the same
JP2008304304A